DYSFUNCTION OF THE VASCULARS ENDOTHELIA IN THE TRAUMATIC BRAIN INJURY - Тамара Ивановна Борщикова; Наталья Николаевна Епифанцева; Сергей Людовикович Кан; Андрей Николаевич Лызлов (Медицина в Кузбассе, 2019)
Objective – in this article to studied of 53 patients with severe traumatic brain injury (TBI) from 1-st to 14 days after trauma. The dynamics of proteins endothelin-1 (ET-1) and the factor von Willebrand (FW) was assessed in groups of patients: survivors and deceased patients and have or not purulent-inflammatory complications. The control group consisted of 21 people. We are study the dynamics of the ET-1 and the FW in the post-traumatic period and determine its roles in predicting of the development of purulent-inflammatory complications and the outcome from TBI.